Determination of Antimicrobial Activity of Antibiotics Encapsulated in Liposomes - Erdene, Enkhtaivan; Dorjbal, Enkhjargal; Baatarkhuu, Oidov; Byambaa, Ariunsanaa (Central Asian Journal of Medical Sciences, 2024)
Objective: Antibiotic-resistant infections caused by bacteria are already a serious concern for humanity, and by 2050, they are most likely to overtake all other causes of death. One of the most frequent causes of skin infections is methicillin-resistant Staphylococcus aureus (MRSA), whose resistance to most medications makes treatment challenging. This study aimed to determine the antibacterial activity of liposome-encapsulated doxycycline compared to free doxycycline. Methods: This study was conducted using an experimental design. Our study isolated and purified the phospholipid (PL) fraction from egg yolk. Antibiotics were encapsulated using the freeze-thaw process, and phospholipids were extracted via intermittent evaporation. Finally, the liposome's minimum inhibitory concentration (MIC) was effective against MRSA. Results: Phospholipid fraction isolated from egg yolks with 32% extraction yield of phosphatidylcholine. The thin phase chromatography fraction was phospholipids with a retention factor (Rf) of 0.39. The effectiveness of liposomal doxycycline hyclate over free doxycycline was demonstrated by in vitro tests. Conclusion: The results showed that a liposome containing phosphatidylcholine could be a tremendous topical antimicrobial construct for treating MRSA infections.